Hubungan Ability To Pay dan Willingness To Pay dengan Kepatuhan Membayar Iuran Peserta BPJS Non PBI di Kecamatan Batang Kuis - Riska Ananda; Fhidiana Sari; Fitriani Pramita Gurning (Lembaga Pengembangan Kinerja Dosen, 2025)
Income factors and the number of dependents in the family have a great influence on the ability to pay, Measurement of the level of ability to pay and willingness to pay (ATP-WTP) is very important to do because it is a factor that affects people in participating in health insurance. Purpose:. This study aims to find out the ability, willingness, public relations of Ability to Pay and Willingness to Pay with compliance with paying contributions of non-PBI BPJS participants in Batang Kuis District. Methods: The type of research used in this study is a quantitative research with a correlation research design that aims to identify the relationship between ability to pay and willingness to pay to the compliance with paying contributions of Non-PBI BPJS participants at the Batang Kuis Health Center. Results: This study found a significant relationship between Ability to Pay (ATP) and Willingness to Pay (WTP) with compliance with paying Non-PBI BPJS contributions, with WTP having a more dominant influence. Participants who have a high willingness to pay tend to be more compliant even though their economic ability is not always high, demonstrating the importance of psychological factors such as awareness and motivation in compliance. Conclusion: In general, this study can be concluded that both factors have a significant influence on the level of compliance of participants. Participants who have a good ability to pay (ATP) tend to be more compliant in fulfilling their BPJS contribution payment obligations, because they are economically able to provide the necessary funds.